Abscisic acid regulates iron accumulation in plant seeds via the PYLs–bHLH IVc–YSLs module - Hongyun Zhao; Juntao Jiang; Cun Wang; Yuan Zheng (Proceedings of the National Academy of Sciences, 2025)
Abscisic acid (ABA) is pivotal in seed development, yet its role in iron (Fe) homeostasis remains unclear. Here, we reveal a PYLs–bHLH IVc–YSLs module that mediates ABA-dependent suppression of seed Fe accumulation in Arabidopsis . During seed maturation, ABA receptors PYLs directly interact with bHLH34/104/115 transcription factors, blocking their binding to YSL1/3 promoters to inhibit Fe transport. Conversely, Fe deficiency triggers bHLH104/115 to repress ABA2 , reducing ABA biosynthesis and PYL expression to derepress YSL1/3 expression—a feedback loop balancing Fe and ABA levels. Genetic analyses confirm that this module governs Fe loading, as ABA-deficient mutants ( aba2-1 , nced6-1 ) and pyr1 pyl124 quadruple mutants accumulate higher Fe, while bhlh34 104 115 phenocopies ysl1 ysl3 Fe deficiency. Our findings establish ABA as a dual regulator that safeguards Fe homeostasis by preventing toxicity during maturation while enabling adaptive Fe storage under deficiency. This mechanistic insight opens avenues for bioengineering crops with enhanced seed Fe content, addressing global nutritional challenges.